Attempted Hanging and Fracture of Hyoid Bone –A Rare Case Report (Indian Internet Journal of Forensic Medicine and Toxicology, 2015)
We present a rare case of attempted hanging with the fracture of hyoid bone. The victim 24 yrs old Hindu male admitted in our hospital as a case of attempted hanging on 30 October, 2013. The x-ray examination revealed fracture of hyoid bone. The rare thing in present case is that the fracture of hyoid bone was seen at the age of 24 yrs. It is contrary to the statement that fracture is seen after the ossification of hyoid bone in the age group of above 40 yrs. It is said ‘once launched upon suicide by hanging, there is no retreat.’ Consciousness is lost as soon as the ligature tightens round the neck, but in present case the victim survived. The details of the case are discussed with the possible cause of fracture of hyoid bone.
Keywords: Attempted hanging; Fracture of hyoid bone; Suicide, Ligature; Vital signs; Greater cornu and Lesser cornu